Analisis Problematika Kurikulum Merdeka pada Pembelajaran Matematika di SDN 012 Babakan Ciparay Kota Bandung - Wanda Fatoni Putri; Dzulfani Nur Hidayanti; Maliq Muzhafran; Ismail Fauzan Ramadhan (Lembaga Pengembangan Kinerja Dosen, 2024)
In Indonesia, the main focus of current education reform efforts is the Merdeka Curriculum. Mathematics is one of the subjects that has undergone many changes, especially at the elementary school (SD) level. This study investigates the impact and challenges that arise when implementing Merdeka Curriculum in mathematics learning at the primary level. The purpose of this study is to provide insights and details regarding the challenges associated with learning mathematics. This research uses a qualitative descriptive methodology that combines two methods to explore information at SDN 012 Babakan Ciparay, Bandung City, which leads to the implementation of the Merdeka Curriculum. The research results obtained in this study found that there were difficulties in implementing the Merdeka Curriculum in students as well as teaching staff, especially in the application of mathematics learning. However, this does not significantly affect the effectiveness of learning and the interest of students and teaching staff.